Culture in the layers of contemporary discourses and historical archives: A review of Anna Maria Lorusso’s Cultural Semiotics - Lenninger, Sara (Public Journal of Semiotics, 2018)
In Anna Maria Lorusso’s book Cultural semiotics: For a cultural perspective in semiotics (Lorusso, 2015) the reader is offered an initiated review of key representatives of 20th century structuralism in semiotics and its entries into poststructuralism, with focus on method of analysis. Related to the theoretical discussions on semiotics and culture, Lorusso offers a series of case studies in semiotic analysis of cultural texts. In this review article, I discuss and evaluate the four strands in cultural semiotics suggested by Lorusso. Further, I draw implications for deciding on the themes and objects of studies in a semiotic realm that focuses on text.